Innovation in Making Pia Cake Skin with the Addition of Purple Sweet Potato (Ipomea Batatas L) in the Village of Kimi, Nabire District - Nurul Magfira Saleh; Nur Al-faida; Gandhi Pratama (International Journal of Public Health, 2024)
Purple sweet potato is one type of tuber. Organoleptic test is a test of a food ingredient based on the level of preference. Shelf life is a time span on a product. Objective: To determine the level of consumer preference and shelf life of pia cake skin with the addition of purple sweet potato (Ipomea Batatas L). Methods: Quantitative research with a completely randomized experimental design (CRD). Panelists in this study were 30 untrained panelists, 15 moderately trained panelists. Results: It is known that the results of research conducted on pia cake skin added purple sweet potato (Ipomea Batatas L) have an effect on the taste p-value 0.01 (<0.05), there is an effect on the aroma p-value 0.02 (<0.05), there is an effect on the color p-value 0.00 (<0.05), there is an effect on the texture p-value 0.00 (<0.05), for the shelf life of pia cake skin in treatments X, Y, V and Z at cold temperature and room temperature there is a relationship p-value <0.05. Conclusion: Based on the results of the study, it can be concluded that there are differences in the variables of taste, aroma, color, texture and shelf life of pia cake skin with the addition of purple sweet potato (Ipomea Batatas L) in Kimi Village, which obtained p-value <0.05. Suggestion: There is a need for skills, knowledge related to purple sweet potatoes to increase creativity and the economy of the community.